Análisis del desgaste mecánico de los revestimientos para los campos floreña y pauto (2018)
In the present work, a methodology of standardization was developed for the simulation of the casing wear in the wells of the Floreña and Pauto fields, with the main objective that the simulation of the wear made adjusted to the real wear that occurs in these wells. These simulations are carried out using the CWEAR software, which allows different options to be used depending on the case of study being carried out. The standarized methodology was established seeking to use the models offered by the simulator that best suit the case of the operational drilling conditions of a well in the aforementioned fields, in addition to using the tubular information from the well casing and the Drill string used to drill them. In this way, the simulation process would be as detailed as possible and would ensure that the simulation resembles the real case more acurately.